Mentoring African American males : a research design comparison perspective - Ross, William (African American male series., 2015)
Mentoring African American Males provides important black male research and student performance data to guide the efforts of those who accept the enormous task of standing in the gap to increase black male achievement. Dr. Ross provides guidance for individuals and institutions embracing the important role of developing mentoring programs or serving as a mentor to youth. However, what makes Dr. Ross' work such a critically important book for any individual or institution considering such a role is its insight into the social-cultural framework within which mentoring must occur at every level from elementary school through college. Equally insightful is the structure that such programs must take in response to the socio-cultural constructs of the families, communities, and institutions where they will occur.There are far more quantitative studies than qualitative on the topic of mentoring. This text addresses that discrepancy and provides the results of several qualitative studies on African American males. There is hardly any that offer a mixed method perspective that combine quantitative and qualitative methodological approaches. This text reports on the research results that are qualitative in nature in addition to some that are from a quantitative and mixed method approach.